A Novel SSR Mitigation Method Based on GCSC in DFIG with Series Connected Compensator - Zakieldeen Elhassan; Li Yang; Tang Yi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presents a novel study for SSR mitigating in the wind power systems based on DFIG using GCSC (Gate controlled series capacitor). The GCSC is composed of three pairs of anti-parallel GTO Thyristors (Gate Turn- off) connected in parallel with a fixed capacitor. The GCSC is applied to reduce inrush current in capacitor compensator during the transient operation by executing a proper firing angle control of thyristor gates. In order to realize SSR oscillation when the transient operation occurred, the DFIG turbine is connected through the shaft turbine model. The simulation results shown that the GCSC device is suitable and reasonable for suppressing SSR caused by torsional interaction (TI) and torque amplification (TA) and also damping the subsynchronous oscillation as well. The transient simulations have been carried out using PSCAD/EMTDC program to demonstrate the capability of the GCSC device in mitigating SSR.